(untitled) (Bangladesh Journal of Plant Taxonomy, 2014)
Hydrocotyle kollimalayensis, a new species is described and illustrated from Kolli hills of South Eastern Ghats, Tamil Nadu, India. The new species is morphologically closer to H. sibthorpioides, but differs from the latter by its filiform stem, glabrous peduncle, shorter petiole and narrower flowers. The most prominent features of the new species Hydrocotyle kollimalayensis are: stem filiform with silky setaceous hairs; leaves sparsely hirsute above and dense below, 5-lobed; flowers 6-12 per inflorescence with glabrous peduncle; and fruits ellipsoidal with 3 obscure ribs. A key to distinguish the new species from other Hydrocotyle species of Tamil Nadu, India is provided. We also inferred the relationship of H. kollimalayensis with allied species using molecular phylogenetic analyses based on nrDNA ITS sequence data. DOI: http://dx.doi.org/10.3329/bjpt.v21i2.21356 Bangladesh J. Plant Taxon. 21(2): 167-173, 2014 (December)